(untitled) (Eurasian Journal of Ecology, 2019)
Abstract. Our research work is aimed at developing effective technologies for the use of Bioorganic fertilizers in forest nurseries of the Aksaу branch of RSI “Ile-Alatau state national natural Park”. The scientific novelty of this article, for the first time stabilized the technology of bioorganic fertilizers in the cultivation of seedlings of tree plants and seedlings of forest nurseries of the Aksai branch of the RSI “IleAlatau State National Natural Park”. The quantitative composition of the main ecological-trophic groups of soil microorganisms of the upper and lower forest nurseries of the Aksai branch of RSU” Ile-Alatau state national natural Park “ has stabilized. Purpose of research – study of the technology of using bioorganic fertilizers for forest nurseries of the Aksay branch of the RSI “Ile-Alatau State National Natural Park”. As a result of the study, it turned out that the length of apricot growth (Prunus armeniaca) in the undergrowth phase increased by 25% in the form of treatment with the PGPR «BioEcoGum» preparation compared to the control form, and increased by 37% in the phase of mass opening of leaves. The growth length of Sivers apples (Malus sieversii) in the phase of sprout formation compared with the control form showed an increase in the form of treatment with «BioEcoGum» PGPR by 32.0%, with a leaf opening phase of 29%. Key words: bioorganic preparation, PGPR bacterium, Microbiology, soil, humus.